Bioassay-guided isolation of vilasinin–type limonoids and phenyl alkene from the leaves of Trichilia gilgiana and their antiplasmodial activities. Issue 19 (21st September 2022) - Kowa, Théodora K.; Jansen, Olivia; Ledoux, Allison; Mamede, Lucia; Wabo, Hippolyte K.; Tchinda, Alembert T.; Genta-Jouve, Gregory; Frédérich, Michel
Abstract: Bioassay-guided fractionation of the CH2 Cl2 -MeOH (1:1) leaves extract of Trichilia gilgiana, yielded two new vilasinin-type limonoids named gilgianin A (1 ) and gilgianin B (2 ), one new phenyl alkene derivative designated as gilgialkene A (3 ), along with six known compounds: rubescin H (4 ), TS3 (5 ), trichirubine A (6 ), sitosteryl-6′- O -undecanoate- β -D-glucoside (7 ), scopoletin (8 ), and octadecane-2-one (9 ). Their structures were elucidated based on spectroscopic analysis and comparison with literature data. Compounds 5 and 6 exhibited the highest antiplasmodial activity with IC50 values of 1.14 and 1.32 μM respectively. Moreover, compound 5 was very cytotoxic with CC50 value of 0.88 µM, compared to compound 6, which was not cytotoxic (CC50 > 10 µg/mL). Compounds 1 ( IC50 = 9.84 µM), 2 (IC50 = 11.04 µM) and 4 (IC50 = 10.71 µM) presented good antiplasmodial activity while also exhibiting significant cytotoxicity, with CC50 values ranging from of 14.45 to 29.7 µM.